Genetic and environmental influence on language impairment in 4-year-old same-sex and opposite-sex twins - Viding, E; Spinath, F; Price, T; Bishop, D; Dale, P; Plomin, R (Blackwell Publishers, 2004)
Background: We investigated the aetiology of language impairment in 579 four year-old twins with low language performance and their co-twins, members of 160 MZ twin pairs, 131 same-sex DZ pairs and 102 opposite-sex DZ pairs. Methods: Language impairment in 4-year-olds was defined by scores below the 15th percentile on a general factor derived from an extensive language test battery. Language impairment of different degrees of severity was investigated by using multiple cut-offs below the 15th percentile. Results: DeFries-Fulker extremes analysis indicated that language impairment as measured by the general language scale is under strong genetic influence. In addition, group differences heritability showed an increasing trend (from 38% to 76%) as a function of severity of language impairment. Although more boys are impaired than girls, incorporating opposite-sex DZ pairs into the analysis found neither quantitative nor qualitative differences between boys and girls in genetic and environmental aetiologies. Conclusions: Language impairment at four years is heritable. This finding replicates previous research on language impairment and extends it by showing that language impairment is heritable in twins selected from a representative community sample. Despite the mean difference between boys and girls, genetic and environmental influences are quantitatively and qualitatively similar for language impairment for boys and girls. For both boys and girls, heritability appears to be greater for more severe language impairment, indicating stronger influence of genes at the lower end of language ability.